Use of Botanical Dietary Supplements in Infants and Children and Their Effects on Health - Seda Çiftçi; F. Gülhan Samur (Hacettepe University, 2017)
Botanical Dietary Supplements (BDS) has an important part in the human diet throughout the history. People, who lived in ancient times, relied on the plants for the treatment of diseases of infants and children. According to World Health Organization, approximately 80 percent of the population who live in developing countries use herbal supplements in order to meet the basic health needs of relies on Botanical Dietary Supplements. These products are used for upper respiratory tract infection, lack of appetite, gastrointestinal disorders, sleep disorders, urinary tract disorders, gynecological diseases and skin diseases in infants and children. Furthermore, not only the medical products but also botanical dietary supplements are used for Attention Deficit Hyperactivity Disorder (ADHD), depression, inflammatory bowel disease, cystic fibrosis, rheumatoid arthritis, along with chronic diseases like asthma or cancer. The most widely used botanical dietary supplements are echinacea, St. John's wort, ginseng and ginkgo biloba. On the other hand, the use of botanical dietary supplements by infants and children may cause side effects and can interact with other drugs. It should be noted that the dosage of botanical supplements for children differs from the dosage for adults. In conclusion, this paper explains which botanical dietary supplements can be used by infants and children and their positive and negative effects on health.